PENERAPAN METODE NAPS (TIDUR SIANG) UNTUK PENINGKATAN KINERJA KARYAWAN JURUSAN KEBIDANAN POLTEKKES KEMENKES PADANG - Nike Sari Oktavia; Faridah Faridah (P3M Universitas Aisyiyah Surakarta, 2022)
Some companies, including Google and Apple allow their employees to take a nap at work, and science proves that this is a very good idea. Studies show that short nap for 10 to 15 minutes increase mental efficiency and productivity, which is a small investment in time for big results in corporate morale and production. The purpose of this community service activity is to identify the benefits of napping for employees of the Department of Midwifery at the Polytechnic of the Ministry of Health in Padang. If they feel the benefits, of course they can apply it on a daily basis during office breaks in addition to prayer and lunch. This Community Service Activity is carried out on September 19 to November 1, 2019. Community Service Activity is carried out every day if employees have time for a nap. Most of the employees consisting of lecturers and education staff feel that taking a naps provides benefits, eliminates fatigue, and makes the body work more enthusiastic because it feels fresher. It is expected that the Department of Midwifery or the Poltekkes of the Ministry of Health in Padang can implement the Naps method or make a nap program in its office.